JENIS DAN MAKNA MAKANAN PADA ACARA BALATAK TANDO DI DESA SUNGAI NANAM KECAMATAN LEMBAH GUMANTI - Fitra, Yelniza; Baidar, Baidar; Fridayati, Lucy (Journal of Home Economics and Tourism, 2016)
The purpose of this study is to identify the type of food, explaining processing techniques, describes the manner of presentation, and express the meaning of food in the event balatak tando. This type of research is qualitative. The place of research in Sungai planted. Sources of data obtained from bundo Kanduang, traditional leaders and local communities. Data collection techniques Snow-Ball Sampling by observation, interviews, and documentation. Analysis of field data reduction, display, conclusion and verification. The results showed that (1) the type of food at the event balatak tando comprises seven types of food, namely: the staple food, side dishes, vegetables, sauce, appendages, fruit and cake or pangacok. (2) Mechanical processing of food in the event balatak tando, fried, boiled, digulai and burned (3) How to serve food at the event balatak tando namely the dish saprah and basanduak. (4) The food at the event balatak tando meaning that all problems should be negotiated or discussed to find trouble spots that should not be decided by one of the family (5) the event balatak tando manduduan alek, eating pangacok, tuka tando, eating rice basanduak.Keywords : Types, Meaning, Food, Balatak Tando